Labor Expectations in the Fractal Era and their Intergenerational Tensions - Alarcón Aragón, María Elena; Iborra Cuéllar, Alejandro (Espergesia, 2026)
The objective of this article was to examine the structural tensions that arose between the job expectations of the new generations (late Millennials and Generation Z) and the operational needs of contemporary organizations. A qualitative methodology was employed, consisting of 32 interviews with students,graduates, middle managers, and executives from different sectors. The results revealed a profound civilizational mismatch, where the liquid, flexible subjectivities of young people clashed with the solid, hierarchical structures of traditional institutions. This conflict was intensified by the accelerated pace of the current environment, which produced non-linear patterns of labor conflict. Among the main tensions identified were the struggle between flexibility and discipline, the contrast between the accelerated growth sought by young people and the slow structures of organizations, and the disconnection between university education and the required meta-competencies. Furthermore, it was observed that emotional health, digital literacy, and epistemic justice played a central role in the sustainability of youth employment. In conclusion, it was determined that young talent constituted an early signal of the future of work, and organizations that adopted adaptive and dialogical models were better prepared to prosper in highly uncertain environments.